Analogical thinking modifiability and math processing strategy - Tzuriel, David (Frontiers in Psychology, 2024)
A sample of 48 children in Grade 2 was randomly assigned to an experimental (n = 24) and a control group (n = 24). Both groups were administered the Analogical Modifiability Puzzle Test (AMPT) and Math Accuracy and Processing Strategy (MAPS) test before and after a teaching phase of the AMPT. The MAPS test includes scores for Accuracy, Processing Strategy, and a Math-Total. The findings reveal significant treatment x time interactions for AMPT (near-transfer) and MAPS (far-transfer) scores. Hierarchical regression analysis showed that AMPT post-teaching score added significantly to Math Total. The findings indicate that Math Accuracy and Math Processing Strategies are affected by mediation for analogical thinking and that modifiability of analogical thinking significantly predicts Math-Total.